2015
DOI: 10.1111/dmcn.12714
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of childhood language disorder: a systematic review

Abstract: ABBREVIATIONS ASDAutism understood. Yet there is increasing evidence that language disorder is associated with differences in brain structure and/or function in core language regions. A key hypothesis has been that children with language disorder do not show the same degree of leftward asymmetry of these regions as observed in typically developing children. We aimed to systematically review structural and functional magnetic resonance imaging (fMRI) studies to examine brain commonalities and differences betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 46 publications
4
80
1
Order By: Relevance
“…It is highly likely that the motor deficits seen in the different developmental conditions, which may not always be distinguishable behaviourally, have differing neural origins, hence the different symptom complexes in these conditions. The neural substrates of motor dysfunction in DCD, ADHD and SLI have not received quite as much attention: there are many hypotheses regarding DCD but few with neurobiological support from brain imaging (see reviews by Brown-Lum &Zwicker, 2015, andGomez &Sirigu, 2015: of these, the corpus callosum, cerebellum, parietal lobe and basal ganglia are highlighted, but studies contain extremely small samples); studies of SLI have mainly focused on perisylvian language cortices (see Mayes, Reilly, & Morgan, 2015 for review, but note that these authors admit the confusion regarding classification of this condition across studies). ADHD and autism are commonly comorbid, both more commonly diagnosed in males 10 and seem to both be characterized by abnormal connectivity (Kern et al, 2015;Konrad & Eickhoff, 2010); they may be set apart by the concentration of dysconnectivity in particular regions.…”
Section: The Neuroanatomical Correlates Of Movement Impairmentmentioning
confidence: 99%
“…It is highly likely that the motor deficits seen in the different developmental conditions, which may not always be distinguishable behaviourally, have differing neural origins, hence the different symptom complexes in these conditions. The neural substrates of motor dysfunction in DCD, ADHD and SLI have not received quite as much attention: there are many hypotheses regarding DCD but few with neurobiological support from brain imaging (see reviews by Brown-Lum &Zwicker, 2015, andGomez &Sirigu, 2015: of these, the corpus callosum, cerebellum, parietal lobe and basal ganglia are highlighted, but studies contain extremely small samples); studies of SLI have mainly focused on perisylvian language cortices (see Mayes, Reilly, & Morgan, 2015 for review, but note that these authors admit the confusion regarding classification of this condition across studies). ADHD and autism are commonly comorbid, both more commonly diagnosed in males 10 and seem to both be characterized by abnormal connectivity (Kern et al, 2015;Konrad & Eickhoff, 2010); they may be set apart by the concentration of dysconnectivity in particular regions.…”
Section: The Neuroanatomical Correlates Of Movement Impairmentmentioning
confidence: 99%
“…Both ASD and ID have been found with gene variants that cause impairment in many aspects of brain development and function, including neurogenesis, neuronal migration, synaptic function, and regulation of transcription and translation (Vissers et al 2016). Mayes et al (2015) found that language impairment in children without ASD was associated with atypical structure and function in traditional language regions including the inferior frontal gyrus, posterior superior temporal gyrus, and caudate nucleus. As noted earlier, Venkataraman et al (2015) reported that ASD included impaired brain connectivity in language regions including right temporal pole, left posterior cingulate cortex, left supramarginal gyrus, and left middle temporal gyrus.…”
Section: Does Asd Have Neurobiological Validity?mentioning
confidence: 99%
“…Likewise, determining familial or disorder-specific risk factors in subgroups of infants at high-risk for ASD may improve the specificity of early identification efforts and investigations of causal pathways (42). For a review of neurobiological language disorder studies see (43, 44). …”
Section: Introductionmentioning
confidence: 99%